2015
DOI: 10.1128/jvi.02513-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Characterization of Recent and Ancient Belgian Pig Group A Rotaviruses and Assessment of Their Evolutionary Relationship with Human Rotaviruses

Abstract: Group) Belgian pig RVA strains and of all completely characterized pig RVAs from around the globe. In contrast to the large diversity of genotypes found for the outer capsid proteins VP4 and VP7, a relatively conserved genotype constellation (I5-R1-C1-M1-A8-N1-T7-E1-H1) was found for the other 9 genes in most pig RVA strains. VP1, VP2, VP3, NSP2, NSP4, and NSP5 genes of porcine RVAs belonged to genotype 1, which is shared with human Wa-like RVAs. However, for most of these gene segments, pig strains clustered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
110
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(133 citation statements)
references
References 50 publications
21
110
0
2
Order By: Relevance
“…In addition, according to da , the high frequency of detection of G5 strains in humans in Brazil may be been linked to porcine-human strain reassortment due to mixed infections. Similar findings were also described recently by Theuns et al who demonstrated a phylogenetic distinction between the genes of porcine and human strains in different subclusters of the tree (Theuns et al, 2015). In this study, the highest relatedness between the VP7-coding gene of porcine and human RVAs was demonstrated for the G9 genotype.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, according to da , the high frequency of detection of G5 strains in humans in Brazil may be been linked to porcine-human strain reassortment due to mixed infections. Similar findings were also described recently by Theuns et al who demonstrated a phylogenetic distinction between the genes of porcine and human strains in different subclusters of the tree (Theuns et al, 2015). In this study, the highest relatedness between the VP7-coding gene of porcine and human RVAs was demonstrated for the G9 genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Reinforcing these results, Theuns et al (2015) described that the VP7-coding genes of contemporary porcine and human G9 strains seem to be much more related to each other than are those of other VP7 genotypes. The close relationship of the VP7-coding genes of porcine and human G9 strains was also demonstrated by the limited number of mutations presented between antigenic regions of the encoded proteins.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Therefore, the HRV-like G9 VP7 genotype of this PRV G9P [13] strain likely emerged from reassortment events (56,57). Recent studies confirmed that some emerging G9 RVs in humans were phylogenetically more similar to PRVs than to earlier human G9 genotypes, suggesting that PRVs are probable sources of heterologous RV infections in humans (22,25).…”
Section: Discussionmentioning
confidence: 87%